'Experience the Second World War like never before!' Game paratextuality between transnational branding and informal learning ('¡Experimenta la Segunda Guerra Mundial como nunca antes!' La paratextualidad de los videojuegos entre el branding transnacional y el aprendizaje informal). Issue 3 (2nd July 2020) - Van Den Heede, Pieter J. B. J.
ABSTRACT: In contemporary historical culture, digital entertainment games about the Second World War have become a prominent format for cultural expression. By allowing players to actively engage with the history of the Second World War, this body of commercial digital entertainment games can significantly co-configure how this war is understood, especially in light of the blurring distinction between formal and informal historical learning. This article presents an interpretative content analysis of the marketing 'paratexts' of a corpus of digital entertainment games about the Second World War that are shared through online game stores and online game community platforms. This is done to provide insight into how digital entertainment games and their online community platforms can function as sites for informal historical learning, both in relation to the history of the Second World War and the central goals of formal history education.